Kewirausahaan Sosial: Studi Kasus PT Kampung Kearifan Indonesia (Javara Indigenious) dan Remaja Mandiri Community (RMC) - Maria Dafrosa Naru (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
Kewirausahaan Sosial: Studi Kasus PT. Kampung Kearifan Indonesia Dan Remaja Mandiri Community Maria Dafrosa Naru.1, Aluisius Hery Pratono.2 Fakultas Bisnis dan Ekonomika, Universitas Surabaya, Surabaya, Indonesia faninaru91@gmail.com1, hpratono@yahoo.com2 Abstract This article seeks to understand the principle of social enterprises by exploring the two case studies in Indonesia. This study adopts qualitative approach by exploring two organizations, which aim to promote sustainable farming industry. The findings address four research questions, including how the social enterprises set their social mission, how they develop product innovation, how the governance practices within their organization, and how they promote fair trade. This article extends the discussion for the emerging concept of social enterprise by highlighting the social mission and social innovation. Keywords: Social entrepreneurship, social mission, product innovation, governance, fair business.